2019
DOI: 10.1165/rcmb.2017-0228oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Microbiome Is Influenced by the Environment and Asthmatic Status in an Equine Model of Asthma

Abstract: Pulmonary, oral and nasal microbiome are influenced by environmental conditions, but only the pulmonary microbiome differs between horses with and without asthma. This difference, mainly present when airway inflammation was present in horses with asthma but not in controls, suggests that the altered lung microbiome in asthma might not be inherent but coincident with inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 28 publications
4
45
0
Order By: Relevance
“…In a previous study, we showed that pulmonary, oral, and nasal microbiota are influenced by environmental conditions, but only the microbiota of the lungs differs between horses with and without asthma . The difference was mainly present when horses with asthma were experiencing exacerbation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a previous study, we showed that pulmonary, oral, and nasal microbiota are influenced by environmental conditions, but only the microbiota of the lungs differs between horses with and without asthma . The difference was mainly present when horses with asthma were experiencing exacerbation.…”
Section: Discussionmentioning
confidence: 85%
“…Fecal samples were collected from a previously described cohort of adult horses with asthma and age-matched controls. 11 Six horses (2 geldings, 4 mares) with a history of reversible episodes of airway obstruction and 6 healthy controls (6 mares) housed in the same barn were enrolled (n = 12). Control horses were considered healthy based on history, physical examination and complete blood count (CBC).…”
Section: Animals and Study Designmentioning
confidence: 99%
“…This has been documented in children and adults with asthma, and dysbiosis is now associated not only with asthma prevalence and acute exacerbation, but also with asthma severity and airway hyperresponsiveness . Dysbiosis of the airways was also described recently using next‐generation sequencing in horses with moderate and severe asthma, using inclusion criteria in line with the current ACVIM recommendations. Tracheal microbiota was altered in horses with moderate asthma, with a greater relative abundance of the genus Streptococcus spp., and pulmonary microbiota was also altered in horses with severe asthma, but without overrepresentation of specific pathogens in bronchoalveolar lavages .…”
Section: Discussionmentioning
confidence: 90%
“…Dysbiosis of the airways was also described recently using next‐generation sequencing in horses with moderate and severe asthma, using inclusion criteria in line with the current ACVIM recommendations. Tracheal microbiota was altered in horses with moderate asthma, with a greater relative abundance of the genus Streptococcus spp., and pulmonary microbiota was also altered in horses with severe asthma, but without overrepresentation of specific pathogens in bronchoalveolar lavages . Neither studies attempted to quantify the absolute amount of specific pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation